PENGARUH FILTRAT ECENG GONDOK (Eichornia crassipes) PADA MEDIA AB MIX TERHADAP PERTUMBUHAN TANAMAN KANGKUNG (Ipomoea reptans, Poir) DENGAN MEDIA HIDROPONIK WICK SYSTEM DAN PEMANFAATANNYA SEBAGAI MEDIA INFORMASI BAGI PENDIDIKAN KE MASYARAKAT - Adi Widodo; Peni Suharti; Lina Listiana (Pedago Biologi : Jurnal Pendidikan dan Pembelajaran Biologi, 2017)
This study to see the effect of the provision aims to filtrate the water hyacinth (Eichornia crassipes) on media AB MIX on the height of plant growth, fresh weight and number of leaves of the plant with Wick Hydroponic System. Treatments ie, control by using AB MIX with 0% filtrate water hyacinth (Eichornia crassipes), AB MIX plus 25% of the filtrate water hyacinth, AB MIX plus 50% filtrate water hyacinth (Eichornia crassipes), AB MIX plus 75 % filtrate water hyacinth (Eichornia crassipes), AB MIX plus 100% filtrate water hyacinth (Eichornia crassipes) and the filtrate water hyacinth (Eichornia crassipes) 100% without AB MIX. The parameters observed plant height, fresh weight and number of leaves of the plant water spinach (Ipomoea reptans, Poir). Plant height and number of leaves are highest in treatment AB MIX written filtrate water hyacinth (Eichornia crassipes) with a concentration of 100% with an average of 21.275 high and the average number of leaves 10. As for the wet weight of kale plants by the filtrate water hyacinth ( Eichornia crassipes) with a concentration of 100% with no nutritional AB MIX provides the greatest impact with the average reaching 1.1325. Based on these results it could be concluded that the filtrate water hyacinth (Eichornia crassipes) had an effect as plant growth regulators naturally on media AB MIX on the growth of high, wet weight and number of leaves of the plant water spinach (Ipomoea reptans. P) with a wick hydroponic system.Keywords: Water Hyacinth (Eichornia crassipes), AB MIX, water spinach (Ipomoea reptans, Poir), Hydroponics